EXAMINING THE COMPONENT OF TRUTH IN ART BASED ON MULLA ṢADRĀ’S OPINIONS - Mahdi Amini; Mojtaba Akhoondi (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2023)
How can the presence of truth in art be philosophically justified? A fundamental question that can be answered in the wisdom of Mullā Ṣadrā, one of the most important philosophers of Islam. The importance of the question of the relationship between art and truth arises from the state of art in the present era. In fact, the degradation of reason in front of feeling from the nineteenth century until today has made the field of arts devoid of any representation of the truth and caused the importance and originality of finding pleasure or evoking feelings in the arts. Therefore, with a philosophical approach and relying on the descriptive-analytical method, at first, it described the fundamental of truth and delusion, the unity of the world, and the known, practical reason and the function of imagination in shaping intellectual concepts based on Mullā Ṣadrā’s views, and then with relying on those principles, he has examined the formation of truth-based works of art. The most important conclusion of the article is that art is not the only product of the feelings and taste of its creator; Rather, the artist, in his understanding of the truth, prepares the ground for its manifestation in the work of art. With this characteristic, art finds a form of rational knowledge, and symbolic and mystical arts are among the most important examples of this type of artistic creation.